2020
DOI: 10.1016/j.cell.2020.08.034
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular Mechanism to Detect and Alleviate Reductive Stress

Abstract: Highlights d Lack of reactive oxygen species, or reductive stress, prevents myogenesis d Reductive stress reverses oxidation of invariant Cys residues in FNIP1 d Only reduced, but not oxidized, FNIP1 is polyubiquitylated by CUL2 FEM1B d FNIP1 degradation leads to activation of mitochondria to recalibrate ROS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 103 publications
10
115
0
Order By: Relevance
“…In addition, our data suggest that FNIP1 could not only regulate mitochondria biogenesis, but also regulate mitochondrial quality. Consistent with this notion, recent study also showed that FNIP1 regulate mitochondrial redox homeostasis [45].…”
Section: Plos Geneticsmentioning
confidence: 56%
“…In addition, our data suggest that FNIP1 could not only regulate mitochondria biogenesis, but also regulate mitochondrial quality. Consistent with this notion, recent study also showed that FNIP1 regulate mitochondrial redox homeostasis [45].…”
Section: Plos Geneticsmentioning
confidence: 56%
“…FLCN/FNIP complex may also play an important role in myoblast differentiation. A recent study identified FNIP1 as a key regulator of myoblast redox homeostasis and integrity (Manford et al, 2020). Under reductive stress, E3 ubiquitin ligase CUL FEM1B binds to reduced cysteines in FNIP1 and induces its degradation by the proteasome.…”
Section: Flcn/mtorc1/tfe3 In Stem Cellsmentioning
confidence: 99%
“…NRF2 can be regulated by targeting reactive cysteine residues in its E3, CUL3 KEAP1 (Zhang et al, 2004), using compounds, such as dimethyl fumarate, which has been approved for the treatment of multiple sclerosis (Dodson et al, 2019). However, inhibition of NRF2 has to be carefully monitored, as persistent stabilization of this transcription factor induces a gene expression program that triggers reductive stress and prevents muscle stem cell differentiation (Manford et al, 2020).…”
Section: Introductionmentioning
confidence: 99%